(untitled) (Perner’s Contacts, 2022)
Open road testing is an essential stage of the process of approving driver assistance and other self-driving functions. However several countries have opened their network with or without limitations for autonomous vehicle testing, there are some sections where the infrastructure was designed to support testing. The aim of this article is to give an overview of such open road testing facilities around the world, introducing the main purposes, the used infrastructure (eg. sensor network, communication) and features (eg. data processing, and control functions), and compare them to the planned investments in Hungary.